ANALISIS ATRIBUT KUALITAS PELAYANAN APARATUR PEMERINTAH DESA DALAM MENINGKATKAN KEPUASAN MASYARAKAT - Sumbawati, Novi Kadewi; Fitriani, F (Samalewa: Jurnal Riset & Kajian Manajemen, 2024)
The purpose of this study was to know the effect of apparatus service on communities’ satisfaction at the Kerato Village Office, Unter Iwes Sub district, Sumbawa District. The type of this study was associative study which aims to know the effect or the relationship between two or more variables. The data used in this study was quantitative data. The type of data used was primary data. The method used to collect data was through questionnaire. The technique of determining sample was used Slovin formula. The numbers of samples in this study were 98 people and were selected randomly. Data analysis was performed using Smart PLS 3.0 M3 Software, including testing the measurement model (outer model) and testing the structural model (inner model). The results of study showed that partially tangible had effect on community satisfaction in Kerato village office, it was based on the value of t-value was higher than t-table (2.288 > 1.290), then reliability had effect on community satisfaction at the Kerato Village Office, it was based on t-value was higher than t-table (1.720 > 1.290), then Responsiveness did not have effect on community satisfaction at the Kerato Village Office, it was based on t-value was lower than t-table (1,197 < 1.290). Furthermore, the value of r square was 0.445 it means that the percentage effect of tangible, realibility and responsiveness on community satisfaction in Kerato village office was 44.5% while the remaining of 54.5% was affected by other variables outside of this study.